Neuroimaging in PRUNE1 syndrome: a mini-review of the literature - Scorrano, Giovanna; Battaglia, Laura; Spiaggia, Rossana; Basile, Antonio; Palmucci, Stefano; Foti, Pietro Valerio; David, Emanuele; Marinangeli, Franco; Mascilini, Ilaria; Corsello, Antonio; Comisi, Francesco; Vittori, Alessandro; et al. (Frontiers in Neurology, 2023)
Prune exopolyphosphatase 1 (PRUNE1) is a short-chain phosphatase that is part of the aspartic acid-histidine-histidine (DHH) family of proteins. PRUNE1 is highly expressed in the central nervous system and is crucially involved in neurodevelopment, cytoskeletal rearrangement, cell migration, and proliferation. Recently, biallelic PRUNE1 variants have been identified in patients with neurodevelopmental disorders, hypotonia, microcephaly, variable cerebral anomalies, and other features. PRUNE1 hypomorphic mutations mainly affect the DHH1 domain, leading to an impactful decrease in enzymatic activity with a loss-of-function mechanism. In this review, we explored both the clinical and radiological spectrum related to PRUNE1 pathogenic variants described to date. Specifically, we focused on neuroradiological findings that, together with clinical phenotypes and genetic data, allow us to best characterize affected children with diagnostic and potential prognostic implications.